Outcomes of outpatient total hip arthroplasty: a systematic review. Issue 1 (January 2021) - Shapira, Jacob; Chen, Sarah L; Rosinsky, Philip J; Maldonado, David R; Lall, Ajay C; Domb, Benjamin G
Introduction: Similar to other total joint arthroplasty procedures, total hip arthroplasty (THA) is shifting to an outpatient setting. The purpose of this study was to analyse outcomes following outpatient THA. Methods: A comprehensive literature search was performed in April 2019 according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines using the PubMed, Embase, and Cochrane databases to identify articles that reported functional outcomes following outpatient total hip arthroplasty (THA). Results: 9 articles, with 683 hips and a collective study period of 1988 to 2016, were included in this analysis. The mean age across all studies was 58.9 years and the follow-up period ranged from 4 weeks to 10 years. 4 studies reported Harris Hip Scores (HHSs) for their patient populations and in 3 studies, the average HHSs were excellent (>90) by 6 weeks postoperatively. The fourth study reported fair HHS scores for the outpatient and inpatient THA groups (75 ± 18, 75 ± 14, p = 0.77, respectively) at 4 weeks postoperatively. VAS scores improved significantly in two studies and NRS at rest and during activity improved significantly ( p < 0.001) in a separate study. Overall, 88.1% of the enrolled patients were discharged the same day of surgery, as expected. Out of the 6 studies reporting on readmissions rate, there were two (0.34%) readmissions within 3 months of surgery. Conclusion: In patients with no significant comorbidities, outpatient THA leads to favourable outcomes as well as low readmission rates in the short term.